Transforming Excavation Finds into Museum Exhibits: Examples from the Byzantine and Christian Museum, Athens - Tsakalos, Antonis (Actual Problems of Theory and History of Art, 2017)
The life of an artefact starts at the moment of its creation, but its real discovery starts at the time of its archaeological acquisition and of its presentation to the public, usually in a museum exhibition. In every step of this long life, the artefact may acquire different uses and meanings, according to the corresponding historical, social, and ideological context. This paper focuses on several examples of the multi-layered and fascinatingprocedure of transforming the excavation finds into museum exhibits. All case-studies have been selectedfrom the different indoor and outdoor exhibitions of the Byzantine and Christian Museum in Athens, Greece. In museum gardens, in the area with cypress trees traditional for cemeteries, the visitors can see three EarlyChristian tombs which were transported there by crane from the excavation site of an ancient cemetery. The metal structure used for the safe transportation of one of the tombs has been conserved and is still visible under the transparent ground level around the tomb. In combination with the information on cemeteries and photo sshowing the transportation of the tombs, it is possible for the visitors to fully understand the procedure between the discovery of antiquities and their presentation in a museum. Moreover, a Late Roman grave uncovered in the museum gardens is now presented in situ, accompanied by relevant photos and textual information. In the museum permanent exhibition, two Early Christian tombs are accompanied by explanatory texts and photos of their discovery during excavations, so that the finds/exhibits can be fully understood in their archaeological and historical context. Last but not least, the well-known ‘Mytilene Hoard’, 7th century, is presented inside the set of two showcases facing each other in order to create an enclosed space, as an allusion to the secret concealment of precious objects in the ground. The above mentioned examples from the Byzantine and Christian Museum reveal the curators’ effort to present the archaeological finds in context, by keeping as much information as possible concerning their discovery and their integration in a museum exhibition.